USE OF ROBOTIC TECHNIQUES IN TEACHING PHYSICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article covers the organization of a physics lesson using modern methods. In this, the intelligence of the student increases by performing laboratory work with the help of robotics.